Endoscopic Ultrasound Can Differentiate High-Grade Pancreatic Intraepithelial Neoplasia, Small Pancreatic Ductal Adenocarcinoma, and Benign Stenosis - Ryota Sagami; Kentaro Yamao; Ryuki Minami; Jun Nakahodo; Hidetoshi Akiyama; Hidefumi Nishikiori; Kazuhiro Mizukami; Kenji Yamao; Vikram Bhatia; Yuji Amano; Kazunari Murakami (Gut and Liver, 2024)
Background/Aims: High-grade pancreatic intraepithelial neoplasia and invasive pancreatic ductal adenocarcinoma ≤10 mm are targets for early detection of pancreatic cancer. However, their imaging characteristics are unknown. We aimed to identify endoscopic ultrasound findings for the detection of these lesions. Methods : Patients diagnosed with high-grade pancreatic intraepithelial neoplasia (n=29), pancreatic ductal adenocarcinoma ≤10 mm (n=11) (who underwent surgical resection), or benign main pancreatic duct stenosis (n=20) between January 2014 and January 2021 were retrospectively included. Six features differentiating these lesions were examined by endoscopic ultrasonography: main pancreatic duct stenosis, upstream main pancreatic duct dilation, hypoechoic areas surrounding the main pancreatic duct irregularities (mottled areas without demarcation or round areas with demarcation), branch duct dilation, prominent lobular segmentation, and atrophy. Interobserver agreement was assessed by two independent observers. Results : Hypoechoic areas surrounding the main pancreatic duct irregularities were observed more frequently in high-grade pancreatic intraepithelial neoplasia (82.8%) and pancreatic ductal adenocarcinoma ≤10 mm (90.9%) than in benign stenosis (15.0%) (p<0.001). High-grade pancreatic intraepithelial neoplasia exhibited mottled hypoechoic areas more frequently (79.3% vs 18.9%, p<0.001), and round hypoechoic areas less frequently (3.4% vs 72.7%, p<0.001), than pancreatic ductal adenocarcinoma ≤10 mm. The sensitivity and specificity of hypoechoic areas for differentiating high-grade pancreatic intraepithelial neoplasia, pancreatic ductal adenocarcinoma ≤10 mm, and benign stenosis were both 85.0%, with moderate interobserver agreement. Conclusion : s: The hypoechoic areas surrounding main pancreatic duct irregularities on endoscopic ultrasound may differentiate between high-grade pancreatic intraepithelial neoplasia, pancreatic ductal adenocarcinoma ≤10 mm, and benign stenosis (Trial Registration: UMIN Clinical Trials Registry (UMIN000044789).